2020
DOI: 10.47895/amp.v54i5.2227
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Determinants of Length of Stay in the Post-anesthesia Care Unit (PACU) at the Philippine General Hospital among Postoperative Patients who Underwent Elective Surgeries to Create a Predictive Model for PACU Length of Stay

Abstract: Background. The aims of this study were to determine the average length of stay in the Post-anesthesia CareUnit (PACU LOS) in the Philippine General Hospital (PGH) and to create a model that will predict the PACU LOSbased on the factors that significantly affect the LOS. Determination and prediction of PACU LOS is essential inresource utilization, and in cost containment and reduction. Addressing the modifiable variables that affect thePACU LOS may lead to an improvement in the LOS of patients in the PACU and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The length of stay in PACU greater than 4 hours (AOR=4.538;95% CI (2.089 -9.857) were strongly correlated with the incidence of PACU complication, our study also observed that patients who encountered PACU complications signi cantly required a prolonged duration of stay than initially planned compared to patients without complications (9,22).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The length of stay in PACU greater than 4 hours (AOR=4.538;95% CI (2.089 -9.857) were strongly correlated with the incidence of PACU complication, our study also observed that patients who encountered PACU complications signi cantly required a prolonged duration of stay than initially planned compared to patients without complications (9,22).…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, the study done in the Philippines revealed that duration of surgery, the occurrence of intraoperative complications, and postoperative complications were identi ed as signi cant predictors for the length of stay at PACU (22).…”
Section: Introductionmentioning
confidence: 99%
“…The length of stay in PACU greater than 4 h (AOR = 4.538; 95% CI: 2.089–9.857) were strongly correlated with the incidence of PACU complication, our study also observed that patients who encountered PACU complications significantly required a prolonged duration of stay than initially planned compared to patients without complications. 9 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the study done in the Philippines revealed that duration of surgery, the occurrence of intraoperative complications, and postoperative complications were identified as significant predictors for the length of stay at PACU. 26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation